Determinants of Bulgarian Brady Bond Prices : An Empirical Assessment - Budina, Nina; Mantchev, Tzvetan (World Bank, Washington, DC, 2015)
To analyze the main determinants of secondary market prices of Bulgarian Brady Bonds, the authors investigate to what extent fluctuations in domestic fundamentals affect the bonds secondary market price. They also assess the extent to which external shocks affect the bonds prices. They estimate the long-term relationship between domestic fundamentals and market prices of bonds, using co-integration techniques. In the long-run, they find that gross foreign reserves and exports had a positive effect on bond prices and the real exchange rate and Mexico's nominal exchange rate depreciation had a negative effect. In the short run, the Asian crisis had a negative impact, and Bulgaria's change in political regime and introduction of a currency board had a positive impact. Mexico's economic crisis in 1995 had contagion effects. The authors' empirical results confirm the view that the so-called fundamentals approach should be used to supplement the analysis of spillover effects for Bulgaria Brady bonds.